An Anthropological Characteristics of Students of The „P. Hilendarski” University at Plovdiv - Bačvarova, Maria (Anthropological Review, 1981)
The author presents anthropometrical characteristics of 300 male and 300 female students examined in 1974 and 1978. Statistical characteristics of the basic body dimensions of the students as well as some comparative data are presented in tables.